Luteoma of Pregnancy with Uterine Leiomyoma as a Diagnostic Challenge and Mimicker of Ovarian Malignancy: A Rare Case From Rural India - S Dayal (JRI, 2022)
Background: Luteoma of pregnancy is a rare, non-neoplastic lesion of the ovary which mimics ovarian tumor. It develops hirsutism or virilization during pregnancy and regresses in postpartum phase spontaneously. A few number of cases are described in literature. The synchronization of ovarian luteoma with uterine leiomyomas is a rare condition; to the best of my knowledge, the association of both conditions is not reported till date. Case Presentation: A 35 year old multiparous woman presented with mass and pain in abdomen came to the gynecology department of Uttar Pradesh University of Medical Sciences in India. On examination, a hard mass in uterus was diagnosed. Ultrasonography revealed a highly vascular uterine adnexal mass possibly arising from ovary with malignant features. Hysterectomy with bilateral salpingo-oophorectomy was done and this specimen with separate mass was sent for histopathology. Right sided ovary was measured 3x3 cm, well demarcated with solid brown areas. CA -125 (cancer antigen -125) level was raised. A separate tumor was measured 15x12x8 cm and it was smooth while cut surface was grey/white with whirling and hemorrhagic foci. Results: The section from ovary revealed luteoma of pregnancy. Endometrium microscopy confirmed pregnancy. Section from another mass/ tumor showed leiomyoma with degenerations. Conclusion: Pregnancy luteoma is a pregnancy induced lesion which mimics malignancy so, it is clinically misinterpreted and over diagnosed. Histopathological investigation is mandatory to diagnose and prevent unnecessary surgeries. The synchronous ovarian luteoma with uterine leiomyoma is a rare condition which represents unusual response to altered hormonal effect in pregnancy; therefore, more studies should be done to understand its pathogenesis.